Analysis of the Skills Gap between Engineering Graduates and the Needs of the Manufacturing Industry in Melaka - Muhammad Syazwan; Nurul Izzah (PT. Berkah Smart Academica, 2026)
The manufacturing sector in Melaka is undergoing a rapid transformation toward Industry 4.0, yet its success is hindered by a significant skills gap between engineering graduates and industrial requirements. This study aims to analyze the dimensions of the skills gap, the impact of Skill-Biased Technological Change (SBTC) as a driver of job polarization, and structural issues such as the